Prosodic detail in Neapolitan Italian - Cangemi, Francesco (Language Science Press, 2014)
Recent findings on phonetic detail have been taken as supporting exemplar-based approaches to prosody. Through four experiments on both produc tion and perception of both melodic and temporal detail in Neapolitan Italian, we show that prosodic detail is not incompatible with abstractionist approaches either. Specifically, we suggest that the exploration of prosodic detail leads to a refined understanding of the relationships between the richly specified and continuously varying phonetic information on one side, and coarse phonologically structured contrasts on the other, thus of fering insights on how pragmatic information is conveyed by prosody.